Perencanaan Struktur Gedung Fakultas Teknik Universitas Moren Jalan Kranggan Semarang - Reinard Sutanto; Willya Moren Wihartono; David Widanto; Budi Setiyadi (G-SMART, 2018)
The construction of engineering faculty at the university of moren can be may be able to meet terms of education facilities.Building of engineering faculty university of moren is school buildings, so that including buildings class viii.The building has six floors of with total building area of 11.664 m2.The roof of the building planned use of concrete plate.The shear wall planned in central structure of the floor ground until the floor 5 to hold earthquake force direction x of 7609 kg.m and direction y of 6879 kg.mA structure for the faculty engineering university moren use 03-1726-2012 sni , SNI T-15-1991-03 , sni 2847-2013 , SNI03-1965-1990, and SNI 07-2529-1991.Planning the structure down include the stake , tiebeam , pilecap .While stuktur upper covering concrete plate  , floor plates , stairs, beam , column , and shearwall .In counting the moments and reaction on buildings it uses 2000 v.14 sofware sapThe results of result in planning the plate with thick 20 cm to floor ground and 12 cm pelat 1 until 5 to the floor and the roof .Design planning a beam B1 = 450 x 700, B2 = 350 x 500 , B3 =350 x 600, B4 = 300 x 450.Design planning a column K1 = 800 x 800.Design planning foundation piles 50 cm in the depth 18 meters